(untitled) (Global Media Journal - German Edition, 2016)
The aim of this essay is to review the status quo of multiculturalism with regard to Muslims and new refugees in Poland. We will point to the critical stance of Poles toward refugees in a situation where there is little experience with them. We will focus on the significant role played by the media and public discussion in shaping an attitude that can be described as outright hostility towards refugees. The perception of immigrants, refugees and ethnic minorities largely depends on the image of them in the media because media has become the main source of information about the ’others’. The essay draws from first results of research conducted in 2015. It contains an exploratory content analysis of Polish media on immigrants and refugees.